Optimal Gait Parameters for Quantifying the Effect of Diagnostic Analgesia in Horses. (June 2014) - Pfau, T; Spicer‐Jenkins, C; Smith, R; Bolt, D; Fiske, Jackson A; Witte, T
Abstract : Introduction: Evaluating responses of horses to diagnostic analgesia is subject to bias. Pelvic movement symmetry can be measured accurately with inertial sensors, but it is unclear which of the many symmetry measures best reflect changes. It was hypothesised that objective parameters mimicking commonly observed visual parameters used by veterinarians (difference between upward/downward sacral movement and between amplitudes of left and right tuber coxa motion) would show the largest, most consistent responses. Methods: 13 horses underwent visual lameness scoring and independent gait assessment with inertial sensors during clinical lameness investigations. Multiple movement symmetry parameters were calculated and changes before/after diagnostic analgesia regressed against change in lameness grade. Confidence intervals of slopes of regression lines were assessed to identify significant changes. Results: All parameters showed variation between horses and across lameness grades. Three measures documented a consistent increase in symmetry for each grade of change in lameness score: difference between sacral displacement minima, and upward movement difference and range of motion difference between the tubera coxae. A change in symmetry of 9–13% for each grade of increase in lameness can be expected. Conclusions: The three most promising pelvic parameters for consistent quantification of changes due to diagnostic analgesia in the hindlimb of lame horses were identified. Difference in upward movement between left and right tuber coxae is the most sensitive but requires simultaneously focusing on pelvic and limb movements and may therefore be more difficult to assess visually. Showing a similar response to diagnostic analgesia, the difference in movement amplitude between left and right tuber coxae may be more easily perceived since it does not require simultaneous focus on limb movement. Ethical Animal Research: The study was approved by the local ethics committee. Explicit owner informed consent for participation in this study is not stated.Sources of funding: None declared.Competing interests: none.